Hydrolyzed collagen interferes with in vitro photoprotective effectiveness of sunscreens - Daniela D'Almeida Peres; Alexandra Hubner; Camila Areias de Oliveira; Tania Santos de Almeida; Telma Mary Kaneko; Vladi Olga Consiglieri; Claudinéia Aparecida Sales de Oliveira Pinto; Maria Valéria Robles Velasco; André Rolim Baby (Universidade de São Paulo, 2017)
ABSTRACT The chronological skin aging is a progressive and natural process with genetic and physiological changes. However, ultraviolet (UV) radiation may accelerate the oxidative stress, generating carcinogenesis and photoaging. Natural compounds and their applications are considered a trend in the cosmetic market. The protein-based film-forming compounds play an important role, once it collaborates for the better distribution of sunscreens on the skin. Here we investigated the in vitro photoprotective effectiveness of sunscreens containing the hydrolyzed collagen associated with UVA, UVB and/or inorganic filters. Sunscreens were developed with octocrylene (7.5%), butyl methoxydibenzoylmethane (avobenzone) (3.0%) and/or titanium dioxide (5.0%), associated or not with the hydrolyzed collagen (3.0%). In vitro photoprotective effectiveness was determined in a Labsphere(r) UV2000S by the establishment of the sun protection factor (SPF) and critical wavelength (nm) values. Physicochemical and organoleptic characteristics were also assayed. The hydrolyzed collagen subjectively improved the formulation sensory characteristics. However, this bioactive compound led to a decrease of the SPF values of the photoprotective formulations containing octocrylene alone and octocrylene + butyl methoxydibenzoylmethane + TiO2. This inadequate interaction may be considered during the development of new sunscreens intended to contain protein-based components.